New morphological and genetic data of Gigantorhynchus echinodiscus (Diesing, 1851) (Acanthocephala: Archiacanthocephala) in the giant anteater Myrmecophaga tridactyla Linnaeus, 1758 (Pilosa: Myrmecophagidae). (December 2019) - Nascimento Gomes, Ana Paula; Cesário, Clarice Silva; Olifiers, Natalie; de Cassia Bianchi, Rita; Maldonado, Arnaldo; Vilela, Roberto do Val
Abstract: Gigantorhynchus echinodiscus (Diesing, 1851) is a parasite of anteaters in South America. Although described by Diesing in 1851, there is still a lack of taxonomic and phylogenetic information regarding this species. In the present study, we redescribe G. echinodiscus collected from a giant anteater, Myrmecophaga tridactyla Linnaeus, 1758, from the Brazilian Cerrado (Savannah) in the State of São Paulo by light and scanning electron microscopy. In addition, phylogenies were inferred from partial DNA gene sequence of the nuclear large subunit ribosomal RNA gene (28S rRNA). We provide for the first time details of the proboscis with a crown having 18 large hooks and numerous small hooks, a lateral papilla at the base of the proboscis, a ringed pseudo-segmented body, large testes, cemented glands in pairs, and a non-segmented region in the posterior end of the body, which contributed to the diagnosis of the species. Molecular phylogenetic analyses recovered G. echinodiscus forming a well-supported monophyletic group with Mediorhynchus sp., which was congruent with morphological studies that allocate both genera within the family Gigantorhynchidae. In conclusion, the present work adds new morphological and molecular information, emphasizing the importance of adopting integrative taxonomic approaches in studies of Acanthocephala. Graphical abstract: Image 1 Highlights: Redescription of Gigantorhynchus echinodischus from Brazilian giant anteater. First molecular data of the genus Gigantorhynchus with 28S rRNA partial gene. Phylogenetic relationships of Gigantorhynchidae are assessed.